Diseño del sistema de gestión ambiental aplicado a los estándares de la ISO 14001:2015 en la constructora Aldava Ingeniería S.A.S (2023)
Companies have a significant environmental responsibility. They must consider their surroundings, activities, processes, and their alignment with environmental aspects. In this book, we will find the process that was carried out to establish an environmental management system at Aldava Ingenieria S.A.S, from its theoretical foundation to its implementation. It begins with the diagnosis conducted through site visits and an examination of the 109 applicable clauses of the ISO 14001:2015 standard, analyzing the data and applying methodological tools such as the SWOT matrix.